REVITALISASI NALAR HUKUM ISLAM: DARI GERAKAN POLITIK MENUJU KESADARAN ETIK - Hijrian A. Prihantoro (UIN Raden Mas Said Surakarta, 2017)
This paper aims to discuss the revitalization of the logical reasoning’s epistemology of Islamic Jurisprudence using the sociology of knowledge' approach as the reconstructive effort to see the relation of the religious text and political context of Indonesian social reality. Based on the historical analysis of the diachronic data, comparing the various political phenomena in the past Islamic history to the nowadays situation, the study revealed that the logical reasoning of Islamic jurisprudence was always related dialectically with the human social life as a fact that Islamic studies have been able to change the paradigm and mindset of the civilization.